Determining the Purchase Situation: A Comprehensive View on Customer Behaviour - Hartmann, Evi; Ritter, Thomas; Gemünden, Hans Georg (Journal of Consumer Behaviour, 2004)
Customer behaviour has moved to the agenda of suppliers' senior management reflecting an increasing strategic attention to benefits that can be gained from management of and cooperation with customers. However, these benefits can only be achieved if the seller's suggested interaction mode matches the purchasing situation of the customer because different approaches are suitable for different purchase situations, i.e. for the specific circumstances the buying firm is in. In this paper, different classification models of purchase situations are analysed in order to identifying the underlying dimensions. Based on a literature review, the authors group the indicators in four dimensions. Then by combining these dimensions an overall integrated classification model is developed.
WiSo-Import:2015-03-26:1230
Keywords: Innovation